Biossorção dos íons cádmio e chumbo pela casca de soja - Colombo, Andréia (2013)
In this study the soybean hulls sorption potential in Cd2+ and Pb2+ in mono and binary component systems has been investigated at batch mode. In order to evaluate the effect of untreated and treated soybean hulls biomass, metal-bearing solution pH, sorption temperature, particle grain size, and agitation velocity on the improvement of the adsorption capacity of Cd2+ and Pb2+ cations, a series of adsorption preliminary tests, in duplicates, were performed. Regarding better sorption conditions, kinetic and equilibrium sorption experiments at batch mode were carried out for both mono and binary component systems. For preliminary and kinetic sorption experiments a series of 125 mL Erlenmeyer-type flask containing 300 mg dried soybean hulls in contact with 50 mL metal-bearing solutions at a 4 mequiv. L-1 concentration of Cd2+ and Pb2+ cations under controlled temperature and agitation velocity in a shaker. Regarding the equilibrium contact time, other sorption experiments, in duplicate, consisting of a series of mixture of 50 mL metal-bearing solutions and 50-1000 mg dried soybean hulls biomass were also performed under controlled temperature and agitation velocity in a shaker. In single component systems, a cation concentration of 4 mequiv. L-1 was tested, while in binary component systems three concentration combination in Cd2+-Pb2+bearing solutions were tested. After each sorption experiment, biosorbent was separated from metal solution by a 0.45 µm pore size membrane filtration system, performing then the determination of Cd and Pb concentrations in diluted liquid samples by flame atomic absorption spectrometry. Sorption tests regarding untreated soybean hulls biomass, pH 5 for Cd2+ and pH 4 for Pb2+, 30oC sorption temperature, a mixture of different particle grain sizes, and 100 rpm agitation velocity have showed the best results on the biosorbent performance to sequestrate Cd2+ and Pb2+ cations from metal-bearing solutions. The kinetic test data have shown that the equilibrium was achieved at contact times of 120 and 180 min for Cd2+ and Pb2+, respectively. Meanwhile, 55 and 64% concentration reductions for Cd2+ and Pb2+, respectively, were also achieved. Furthermore, the pseudo-second order kinetic model has fitted better the sorption kinetic data for both tested divalent cations. The equilibrium sorption data for mono-component systems have been well fitted by the Langmuir isotherm model, with maximum sorption capacity (qmax) of 0.5091 ± 0.0054 mequiv.g-1 and 0.6577 ± 0.0218 mequiv.g-1 for Cd2+ and Pb2+, respectively. Bicomponent equilibrium data were graphically represented by a 3D adsorption surface and modeled by a modified extended-to-multicomponent Langmuir-type isotherm, obtaining good fits. The results indicates that each component maximum capacity depends on the other species at the solution, inasmuch total adsorption capacity remains constant. Besides, a second component at the solution influences the isotherm curve shape. Thus, based on sorption results, untreated soybean hulls biomass is an alternative low-cost biosorbent to be applied in treatment systems of industrial effluents containing high concentration of Cd2+ and Pb2+ cations.